2015
DOI: 10.1016/j.celrep.2015.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Functional Redundancy of ERK1 and ERK2 MAP Kinases during Development

Abstract: ERK1 and ERK2 are the effector kinases of the ERK1/2 MAP-kinase signaling pathway, which plays a central role in transducing signals controlling cell proliferation, differentiation, and survival. Deregulated activity of the ERK1/2 pathway is linked to a group of developmental syndromes and contributes to the pathogenesis of various human diseases. One fundamental question that remains unaddressed is whether ERK1 and ERK2 have evolved unique physiological functions or whether they are used redundantly to reach … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
94
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(103 citation statements)
references
References 30 publications
8
94
0
1
Order By: Relevance
“…Activated Erk1/2 is observable in the limb bud mesenchyme, and AER and has been shown to depend on Fgfr signaling (Corson et al 2003). Hindlimb agenesis accompanied by distal forelimb defects is also observed in conditional mutants that lack Mapk1 in the embryo proper (Fremin et al 2015). It is not known why loss of Mapk1 produces more severe defects in hindlimb development, although this may suggest that forelimbs and hindlimbs require different levels of Erk1/2 signaling.…”
Section: Fgf-erk1/2 Signaling Regulates Epithelial-mesenchymal Interamentioning
confidence: 95%
See 2 more Smart Citations
“…Activated Erk1/2 is observable in the limb bud mesenchyme, and AER and has been shown to depend on Fgfr signaling (Corson et al 2003). Hindlimb agenesis accompanied by distal forelimb defects is also observed in conditional mutants that lack Mapk1 in the embryo proper (Fremin et al 2015). It is not known why loss of Mapk1 produces more severe defects in hindlimb development, although this may suggest that forelimbs and hindlimbs require different levels of Erk1/2 signaling.…”
Section: Fgf-erk1/2 Signaling Regulates Epithelial-mesenchymal Interamentioning
confidence: 95%
“…However, results from this approach may be difficult to interpret, as many biological contexts require signaling through multiple RTKs. For example, the labyrinth compartment of the placenta requires Fgfr2, Met, Egfr, Igf1r, and many signaling pathways, including p38α, Erk1/2, and Akt (Liu et al 1993;Bladt et al 1995;Sibilia and Wagner 1995;Threadgill et al 1995;Xu et al 1998b;Adams et al 2000;Mudgett et al 2000;Hatano et al 2003;Yang et al 2003Yang et al , 2005Fremin et al 2015). Since Fgfr2 is capable of engaging all of these pathways, it is difficult to know whether Fgfr2-associated placental defects are simply due to decreases in Erk1/2 signaling or whether these phenotypes are the result of lowering the activity of multiple signaling pathways.…”
Section: Considerations and Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The CRISPR/Cas system seems to be more efficient than the TALENs (Table S1). Due to the redundant role of Erk1 and Erk2 (34), it is necessary to generate Erk1 and Erk2 double KO ESCs to study the function of Erk signaling. Thus, we attempted to knock out Erk1 and Erk2 in Erk2 −/− and Erk1 −/− ESCs, respectively.…”
Section: Significancementioning
confidence: 99%
“…These strong phenotypic differences suggested that ERK2 may play a more significant role in mouse development or that temporal or quantitative expression of the genes differed during development. ERK2 protein is generally expressed at higher levels than ERK1 levels in most mammalian tissues (Fremin, Saba-El-Leil, Levesque, Ang, & Meloche, 2015). Numerous studies in cells and mice using knockdown and knockout strategies have suggested specific individual biological functions for ERK1 or ERK2 based on observations when one protein or the other is lost.…”
Section: Erk1 and Erk2mentioning
confidence: 99%